Jordan Student Aid Reform : Opportunities for a New Generation - Alkhoja, Ghassan; Dawani, Zaina; Shanti, Ehab (World Bank, Washington, DC, 2012)
This is the case in Jordan and this quick note is based on a study to better inform decision-makers on policy options regarding the development and expansion of student aid programs in Jordan. The goal was to give voice to primary stakeholders and allow them to participate in the process, express their views and concerns and thus become active partners in the programs rather than passive recipients to pre-determined activities. The specific objectives of the study were to assess: 1) how university undergraduate students finance their higher education and the extent to which they and their families take out existing (student or consumer) bank loans; 2) how secondary students in their final year of study plan to finance their higher education; 3) the demand for student loans among university and higher education students and the potential demand among secondary students; 4) the degree to which financial barriers keep eligible students from continuing on to higher education or on to their institution of choice; and 5) the degree to which access to loans or other types of educational finance would influence students' decision to go on to higher education or to study in a higher cost discipline.